Low dose (d1-5/7) oral etoposide regimen in intensively treated platinum-resistant epithelial ovarian cancer: The İzmir oncology group (IZOG) study (Annals of Medical Research, 2021)
Aim: Oral etoposide dosage is roughly 50-100 mg/m2 on days 1 to 21 every 28 days. However, dosage of 50 mg/day oral etoposide for five days a week is not well published. The present study, aimed to evaluate the efficacy and toxicity profile of low dose oral etoposide regimen (50 mg/day on days 1 to 5 every week) in platinum-resistant epithelial ovarian cancer (EOC).Material and Methods: This study retrospectively evaluates patients with pathologically confirmed platinum-resistant EOC who were unable to tolerate the standard oral etoposide regimen and were on low dose (d1-5/7) oral etoposide regimen in third line or beyond within the period between 2006 and 2014.Results: The overall response rate among 33 EOC patients was 15.1% while clinical benefit rate was 42.4% (stable disease in 27.3% and partial response in 15.1%). Median progression-free survival was 4 months (95% confidence interval [CI], 2.8–5.1 months) and median overall survival was 12 months (95% CI, 8.8–15.1 months). Conclusion: We concluded that low dose oral etoposide (50 mg/day, on days 1 to 5 every week) was effective and well tolerated for platinum-resistant EOC.